Case Study: Learning Difficulties of Qualitative Research Methodology at Biology Education Postgraduate - Evi Kristiana (Universitas Muhammadiyah Mataram, 2020)
Qualitative research methodology courses become a provision for postgraduate students to carry out research, as one of the three obligations of college. The course is a new subject and most students had never practiced it and had never been familiar with the concepts. The aims of the study is to analyzed the causes of learning difficulties and solutions carried out by students and by lecturers in qualitative research methodology courses. This study used a qualitative research approach with a case study design. Data were obtained from questionnaires and interviews with 20 postgraduate students of biology education, Universitas Negeri Malang. Data processing consists of: data reduction, data presentation, and making conclusions. The students experienced main problems in understanding the teaching materials used because it was written in English and the methods in various qualitative studies tend to be similar so causing confusion. Various solutions are carried out by students, for example: conducting discussions, compiling concept maps, and conducting qualitative research practices. Supporting lecturers have main difficulty in assessment. Lecturers take advantage of online media to facilitate assessment. The findings of this study provided alternative solutions for lecturers and students who take qualitative research methodology courses in order to minimize the constraints.